Ethylene degreening treatment of ‘Ponkan’ tangerine in the north of the Minas Gerais State, Brazil - dos Santos da Costa, Marcio Gama; Chamhum Salomão, Luiz Carlos; Lopes de Siqueira, Dalmo; Cecon, Paulo Roberto; Fernandes Aquino, César; Rosa de Lins, Leila Cristina; Ribeiro Alves, Robson (Comunicata Scientiae, 2018)
The objective of the study was to elucidate the best combination of ethylene dose and exposure time aiming the degreening of ‘Ponkan’ tangerines. Fruits harvested with fully green peel were placed in airtight boxes, exposed during 24, 48 and 96 h to ethylene gas at concentrations of 0, 5, 10, 20 and 40 µL L-1, at a temperature of 20 ± 1°C and 90 ± 5% of relative humidity. On every 24 h the fruits were evaluated for color, Hue angle, total chlorophyll and carotenoids in the peel, solutes leakage, soluble solids, titrable acidity, CO2 production and fresh fruit weight loss. The degreening was more pronounced in fruits exposed to ethylene for 96 h, independently the concentration. The electrolytes leakage peel increased linearly in fruit-control and those exposed to ethylene for 24 h. In fruits treated for 48 and 96 h, electrolyte leakage was observed only during ethylene exposure. The accumulated fresh mass loss did not exceeded 1% in the fruits. The ethylene dose did not affected the fruit respiratory behavior. The best combination aiming fruit degreening was the exposure during 96 h with 5 μL L-1 of ethylene, followed by 48 to 72 hours of storage after treatment.